2007
DOI: 10.1128/aem.02616-06
|View full text |Cite
|
Sign up to set email alerts
|

Differences between Bacterial Communities in the Gut of a Soil-Feeding Termite (Cubitermes niokoloensis) and Its Mounds

Abstract: In tropical ecosystems, termite mound soils constitute an important soil compartment covering around 10% of African soils. Previous studies have shown (S. Fall, S. Nazaret, J. L. Chotte, and A. Brauman, Microb. Ecol. 28: [191][192][193][194][195][196][197][198][199] 2004) that the bacterial genetic structure of the mounds of soil-feeding termites (Cubitermes niokoloensis) is different from that of their surrounding soil. The aim of this study was to characterize the specificity of bacterial communities within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 37 publications
6
39
1
Order By: Relevance
“…Members of the Alphaproteobacteria, Betaproteobacteria, Gammaproteobacteria, and Firmicutes were found, with some variation in the species recorded, depending on the method used. These results were in accordance with previous reports of microbes associated with insects, including Drosophila (17), mosquitoes (56), and termites (27). Although the main bacterial phyla are shared with many other arthropod lineages, we found that native A. tabida populations harbor a microbial community dominated by the genera Wolbachia and Rickettsia, in the order Rickettsiales.…”
Section: Discussionsupporting
confidence: 83%
“…Members of the Alphaproteobacteria, Betaproteobacteria, Gammaproteobacteria, and Firmicutes were found, with some variation in the species recorded, depending on the method used. These results were in accordance with previous reports of microbes associated with insects, including Drosophila (17), mosquitoes (56), and termites (27). Although the main bacterial phyla are shared with many other arthropod lineages, we found that native A. tabida populations harbor a microbial community dominated by the genera Wolbachia and Rickettsia, in the order Rickettsiales.…”
Section: Discussionsupporting
confidence: 83%
“…This study demonstrated that there was no obvious relationship between food microflora and gut actinobacterial community. This agrees with previous studies which stated that there was no substantial overlap between gut microbial communities in soil-feeding termites and the surrounding soils used as natural food (Donovan et al, 2004;Fall et al, 2007). Furthermore, since the identity of comigrating bands was confirmed by nucleotide sequencing of DGGE bands, the large number of fragments detected in the DGGE profiles can be considered as an indication of the presence of diverse actinobacteria taxa in the gut.…”
Section: Discussionsupporting
confidence: 78%
“…The method described by Fall., et al [7] was adopted for sample preparation. Using a sterile syringe, a 9ml of sterile distilled water was dispensed into 3 different test tubes under aseptic conditions and a 1g of the termitarium was poured into the first test tube, homogenized and a 1 ml was taken out for a serial dilution procedure till the 5th dilution was obtained.…”
Section: Methodsmentioning
confidence: 99%
“…However, only a few reports are available on the microbial diversity of termitarium [7]. In this study, there is need for exploration of this nest in other to know the possibility of discovering novel microorganisms.…”
Section: Bacteria Isolates From Termitarium and Cocoa Barkmentioning
confidence: 99%